Análise do fenômeno da declinação na entonação de sentenças declarativas isoladas dos falantes do português brasileiro - Karine Kellvia de Souza (2007)
This dissertation had as central task to analyze the occurrence of the phenomenon of fundamental frequency declination in isolated declarative sentences by Brazilian Portuguese speakers in Belo Horizonte. Declination is characterized as the gradual decline of F0 values towards the end of an utterance. This is an experimental study that investigates declination - under the phonetic point of view, as a phenomenon observed in many languages - by means of the qualitative and quantitative analysis of 260 sentences pronounced for 13 informers. Twovariables were chosen for the corpus: i) declarative sentences with ii) short and long extension. The initial hypothesis was that declination in short sentences was larger than in the long ones. The data - fundamental frequency values in relation to time - has been collected using the program Winpitch and submitted to a linear regression analysis. The results provide evidence for the occurrence of the phenomenon in short declarative sentences as much as in long ones with no statistical difference between them, which ran counter the initial hypothesis raised by the researcher. The present study not only certifies the relevance of declination as a trend of the language and the presence of the phenomenon in isolated declarative sentences independent of their extension, contrary to a conception defended by many, that declination ismostly present in short sentences.